Microfinance governance: a systematic review and future research directions. Issue 7 (29th April 2020) - Rasel, Md. Ali; Win, Sandar
Abstract : Purpose: The purpose of this article is to systematically review extant research on the corporate governance (CG) of microfinance institutions (MFIs) from a global perspective. In the process, it discusses scholarly contributions and highlights key issues from the findings of past studies on several governance attributes, in particular, their interconnections and influence on different institutional outcomes of the sector. Design/methodology/approach: Although academic work on microfinance governance is substantial, prior studies lack a comprehensive approach to reviewing the literature on this topic. We adopted a systematic method to review past studies on microfinance CG by applying particular inclusion and exclusion criteria. In this regard, the study developed specific questions and sought to find their answers from the existing literature. Findings: The findings from our research indicate that microfinance governance-performance relationship is the central focus of the majority of our reviewed papers, although a few attempts have been made to explain the interconnection between CG mechanisms at the firm and institutional level. Our findings also show that existing studies have used a variety of techniques to measure MFI performance vis-à-vis their hybrid mission, such as profitability and outreach. Moreover, the study found that common topics discussed in the mainstream literature include board structure, CEO characteristics, audit quality, external governance, disclosure and MFI ownership type. Research limitations/implications: This review has some limitations that warrant further research. First, we considered only peer-reviewed scientific publications for our systematic review. Second, we omitted non-English journal papers from our sample. In light of these limitations, we provide some future research directions that may shed further light on our current inquiry. Originality/value: This paper evaluates past relevant studies using a systematic approach (in preference to the commonly used narrative approach) for a span of over eighteen years; thereby contributing significantly to the sectoral governance literature. This study is novel in that it offers new incentives and opportunities for further research in order to meet the shortcomings of reviewed papers from various theoretical, empirical, methodological and geographical standpoints.